Country Partnership Strategy (FY2013–2017) for the Republic of Senegal - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2405685:YH9WZL9A

Joint IDA-IFC-MIGA Country Partnership Strategy for the Republic of Senegal - World Bank (2013)
KerkoCite.ItemAlsoKnownAs: 2339240:3REHP3V4 2405685:FT6M9626

Towards Localization of Automated Tutors for Developing Countries - Zualkernan, Imran; Arroyo, Ivon; Woolf, Beverly P. (2013)
Abstract. This paper describes localization issues in relation to AIED systems in the developing world, and analyzes the particular case of the successful immersion of learning technologies to schools in Pakistan. The paper analyzes the needs for personalized learning in the developing world in comparison to countries such as the United States. A model and a survey based on various types of localization dimensions like teacher, student, and cultural alignment was developed and deployed to conduct an evaluation of an AI tutor called the Wayang Outpost in Pakistan. The results are that teachers are likely to use such a system if available, and that their intention to use such a tutor in the future is strongly dependent on how well the tutor is aligned with their teaching practices, students ’ learning habits, and whether the language in the tutor is understood by students. On average these teachers were also willing to allocate about two hours per week for such automated tutors.
KerkoCite.ItemAlsoKnownAs: 2339240:BSFMA2FT 2405685:CZR7Q4AJ
Keywords: ⛔ No DOI found

Implementation of Information and Communication Technologies (ICTs) in Education Course: A Case from Teacher Education Institutions in Pakistan - Majoka, Muhammad Iqbal; Fazal, Shawana; Khan, Muhammad Saeed (Bulletin of Education and Research, 2013)
This research was aimed to explore the implementation of Information and Communication Technologies (ICTs) in education in teacher training programs in the Khyber Pakthunkhwa and Punjab provinces in Pakistan. It was the first time that the course "ICTs in Education" was implemented for ADE/B. Ed (Elementary) programs in session 2010-11. In this situation, it was vital to explore how successfully this course was implemented in the pioneer institutions, so as to have baseline information for further improvement in the implementation process. This study was focused to explore: (i) How the course "ICTs in Education" was implemented? (ii) How did the teacher educators follow the course guide and to what extent the course guide was helpful in implementing this course? Seven teacher training institutions (three from the Punjab and four from KP provinces) were selected as target population. The total sample was 40 teacher educators and 200 students from seven institutions. Mixed method research design was adopted to conduct this study. The data was drawn from the surveys for heads and prospective teachers, and semi-structured interviews with teacher educators. Analysis revealed that only in a few classrooms, different activities/ experiences as suggested in the unit were properly implemented, while in most that was not the case due to issues such as shortage of electric power supply, scarcity of ICTs tools and lack of training and skills in ICTs application. The extent to which teachers followed the course guide was another factor contributing to the implementation process.
Publisher: Institute of Education and Research KerkoCite.ItemAlsoKnownAs: 2339240:ZE68BKG6 2405685:SEX5IS4Z
Keywords: Barriers; Energy; Foreign Countries; Guides; Information Technology; Program Implementation; Teacher Education Programs; Teacher Educators; ⛔ No DOI found

The Impact of Learning Design on Student Learning in Technology Integrated Lessons - Waqar, Yasira (Procedia - Social and Behavioral Sciences, 2013)
The purpose of this paper is to investigate the impact of learning design on knowledge transfer in technology integrated lessons where limited technologies are available to students in a third world country. This article includes an evaluation of the learning designs of technology integrated lessons in a private school in Pakistan. Qualitative research methodologies were employed to see the impact of learning design on knowledge transfer of students when similar technologies are used at the same grade level but the learning designs are different. The results revealed that knowledge transfer depends on learning design in technology integrated lessons where limited technologies are available. In third world countries like Pakistan the concept of technology integration in schools is relatively new and the schools do not have access to sophisticated online learning environments like agent based learning or environments where in built scaffolds are provided to students. So technologies like Microsoft office, videos, digital cameras and projector are being used in private schools to improve the teaching and learning experience of students and learning design plays a very important role in knowledge transfer.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.sbspro.2013.10.119 2339240:7IYXTSDK 2405685:5JEF7XEX

Preparing Future Teachers through Distance Learning: An Empirical Study on Students' Perception of Teacher Education Program Provided by AIOU Pakistan - Nadeem, Mohammed; Ali, Akhtar; Maqbool, Saira (Turkish Online Journal of Distance Education, 2013)
The purpose of the current study was to analyse the pre service teachers training programs for the distance learners of Allama Iqbal Open University (AIOU) Islamabad, Pakistan. This kind of training is provided to the future teachers enrolled to acquire pre service training to become a teacher in a Government educational institution in Pakistan. The data was collected by administering a 45 items agree disagree four points Likert type scale to the subjects mainly through the scheduled meetings during the workshops. The independent sample t-test, and one way ANOVA along with mean difference was worked out for the data set. A group of 490 student teachers were randomly selected from the regions of Bahawalpur, Bahawalnagar, Rahimyarkhan, Multan, and D.G.Khan Districts (Southern Punjab). The planning for training is made timely but lacking physical facilities remains dominant in trainings. Although training plays an important role in students learning yet it is considered just a routine activity which made it a useless exercise. Similarly, findings reveal that co-curricular activities and child psychology are those aspects which ignored in the training. Future studies may be aimed at comparing the training system of teachers with teacher training through other channels of formal system of governments.
Publisher: Anadolu University KerkoCite.ItemAlsoKnownAs: 2339240:VA5S33ZR 2405685:MMLNNP88
Keywords: Child Psychology; Distance Education; Educational Facilities; Foreign Countries; Likert Scales; Measures (Individuals); Meetings; Open Universities; Statistical Analysis; Student Teacher Attitudes; Student Teachers; Teacher Education Programs; Workshops; ⛔ No DOI found

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...
Library Catalog: blogs.worldbank.org KerkoCite.ItemAlsoKnownAs: 2339240:5I5XNP44 2339240:7ENMXVAZ 2339240:7TDXW2WT 2339240:M7NFMPY5 2405685:23SM2GHY 2405685:2KLF59UJ 2405685:4QHLLY7H 2405685:BJSJWEMM 2405685:EJG6JBSL 2405685:EY7WAUHY 2405685:MDR3XLXP 2405685:N584ISNZ 2405685:RCHYAVL3 2405685:SVDWLWHS 2405685:XED3H9S7 4042040:MXSNKXZ5 4656463:P4BDEDD3 4656463:YXDWWIE2